The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1097/00002508-200103000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Perspectives on the Relation Between Catastrophizing and Pain

Abstract: The tendency to "catastrophize" during painful stimulation contributes to more intense pain experience and increased emotional distress. Catastrophizing has been broadly conceived as an exaggerated negative "mental set" brought to bear during painful experiences. Although findings have been consistent in showing a relation between catastrophizing and pain, research in this area has proceeded in the relative absence of a guiding theoretical framework. This article reviews the literature on the relation between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

93
1,702
11
60

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 2,053 publications
(1,866 citation statements)
references
References 90 publications
93
1,702
11
60
Order By: Relevance
“…34 Thus, the tendency to catastrophize about the impending surgical experience and anticipated pain increases distress and may contribute to a more intense pain experience. 18 As anxiety increases preoperatively, patient preoperative quality of life suffers inversely. 21 Recent studies have revealed that pre-surgical pain catastrophizing is a unique predictor of immediate post-surgical pain and the severity of pain up to six weeks after surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 Thus, the tendency to catastrophize about the impending surgical experience and anticipated pain increases distress and may contribute to a more intense pain experience. 18 As anxiety increases preoperatively, patient preoperative quality of life suffers inversely. 21 Recent studies have revealed that pre-surgical pain catastrophizing is a unique predictor of immediate post-surgical pain and the severity of pain up to six weeks after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Pain catastrophizing is associated with a multitude of pain-related outcomes, including pain severity, decreased pain tolerance, increased post-surgical pain, increased analgesic consumption, and somatization. [15][16][17][18] High levels of pain-related anxiety has also been associated with greater pain severity, disability, and lower quality of life. 19 Patient factors, such as female sex and younger age, are correlated with heightened fear-based states that lead to increased perioperative pain and anxiety.…”
Section: Résumémentioning
confidence: 99%
“…The communal coping model (CCM) of pain suggests that expressions of pain to significant others may serve to evoke particular responses, such as assistance (Sullivan et al, 2001). Further, operant learning theory asserts that partners can directly influence a person's pain experience and associated disability (Fordyce, 1976).…”
Section: Partner Responses To Pain and Sexual Functioningmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] FAB refer to the fear-induced avoidance of movements or activities which are expected to be painful, whereas catastrophizing is defined as an exaggerated negative mental state related to an actual or anticipated painful experience. [1][2][3][4][5][6][7][8][9] In the Spanish cultural environment, FAB have shown to have an either negligible or nonexistent influence on LBP among elderly populations and among acute, subacute and chronic LBP patients treated in routine practice, [10][11][12][13] whereas catastrophizing correlates with disability and explains approximately one fourth of its variance, 13,14 suggesting that it may have an influence on the prognosis of LBP patients.…”
Section: Introductionmentioning
confidence: 99%